Knowledge vs. Morality Which Is More Important?: According to the Views of Ustadz Abdul Somad and Ustadz Adi Hidayat - Alihan Satra; Mujila; Afrina Salsabilla; Balkis Adelia; Meiliza Amelia Andariska (The Future of Education Journal, 2025)
The article "Knowledge vs. Morality: A Study of Ustadz Adi Hidayat and Ustadz Abdul Somad" explores the fundamental relationship between knowledge and morality in the life of a Muslim, emphasizing that these two aspects are inherently interconnected and inseparable. The purpose of this study is to understand and explain how the relationship between knowledge and morality is viewed in Islam. This research uses a source triangulation method, comparing and validating data from various sources to ensure reliability—drawing from the lectures of Ustadz Abdul Somad and Ustadz Adi Hidayat, as well as relevant academic literature. The results indicate that knowledge and ethics are strongly linked in building a sustainable human civilization. Scientific advancement without moral awareness can lead to negative consequences, such as social and environmental damage. As a result, researchers have an ethical responsibility to ensure that their discoveries not only offer practical benefits but also uphold human values.